Efek Pemberian Mikroorganisme Selulolitik (MOS) dan Pupuk Anorganik Terhadap Pertumbuhan Tanaman Kelapa Sawit(Elaeis guineensis Jacq.) pada TBM-III - Saputra, Sukemi Indra; ', Rianto1; ', Gusmawartati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The study aims to determine the interaction effect of cellulolytic microorganisms and inorganic fertilizer on the growth of Palm Oil plantations in the TBM-III. This study lasted from April to July 2013 at PT. Tunggal Perkasa Plantation, Air Molek, Pasir Penyu District, Indragiri Hulu, Riau Province. Research arranged experimentally using a  Randomized Block Design (RBD) with two factors:  cellulolytic microorganisms and inorganic fertilizers with 3 replications. Data were analyzed using ANOVA and followed by further test DNMRT at 5% level. The parameters measured were plant height, stem girth, number of leaves, length of rachis, petiola length, leaf width, and leaf length. The results shows that by giving cellulolytic microorganisms and inorganic fertilizers on Palm Oil at the age 30 months significantly affect the growth of plant height, stem girth, length of rachis, petiola length, leaf width and young leaf length, then the inorganic fertilizer 1 x high-dose recommendation can increase plant height, number of leaves, the rachis length, petiola length and width of  young leaf in oil palm plantations, otherwise by giving cellulolytic microorganisms reveal non significantly different on all parameters except palm oil height at the age            30 months. Keywords: Cellulolytic microorganisms, inorganic fertilizer, Palm Oil